Derivative Spectrophotometric Estimation of Amoxycillin and Bromhexine Hydrochloride in Tablets - Kumar Gupta, Arun; Kaskhedikar, S.G. (Asian Journal of Chemistry, 2010)
A simple, accurate, economical and reproducible procedure for simultaneous estimation of amoxycillin and bromhexine hydrochloride in two component tablet formulations has been developed. The method was based on derivatisation of fundamental spectra in first order to eliminate the spectral interference from one of the two drugs while estimating the other and measure absorbance at two wavelengths 278.8 and 326.2 nm. Beer's law was obeyed in the concentration range of 0.0 to 375.0 mcg/mL of amoxycillin and 0.0-100.0 mcg/mL of bromhexine hydrochloride. The results of analysis obtained in triplicate of experiment with two different compositions of tablet formulation were validated statistically and by recovery studies.